Innovative PhD-DNP Faculty Collaboration to Advance Baccalaureate Student Population Health Competencies. Issue 5 (September 2018) - Mauro, Ann Marie P.; Tracey, Debora L.; LoGrippo, Maria Torchia; Brienza-Arcilla, Diane; Williams-Gregory, Mona; Shugg, Suzanne; Bravo, Angelica; Byrne, Claire
Abstract : Abstract: Entry-level nurses require health promotion, chronic disease self-management, care coordination, data utilization, and evidence translation competencies to address complex population health needs. An innovative PhD-DNP faculty collaboration implemented a descriptive survey design to evaluate simulation-based strategies using an unfolding chronically ill adult case to address population health. Results showed the PhD-DNP faculty team was effective in developing clinically meaningful learning experiences to assist baccalaureate students to develop population health competencies. This project provides strong evidence supporting the value and positive impact of engaging faculty from research and practice for future educational research. Abstract : Supplemental digital content is available in the text.